English Mainstream Texts and Specifics of Their Discourse Expansion - E. V. Terekhova (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The paper discusses English mainstream discourse specifics and its expanding under the lens of collocations. With discourse definition being provided, discourse vs text differences are reviewed. Based on the mainstream discourse definition, collocation examples borrowed from the authentic English sources have been collected and studied. The paper analysis is focused on featuring their semantics, with some of the examples undergoing reinterpretation of the words’ direct meaning. Other cases are emphasized as hard to reveal the direct meaning due to lack of information transparency or triviality conveyed by a marked out component of the collocation. The scientific originality of the study is expected to be found in the way the authors verbalize the information. The specific intentions are conveyed by “ packing ” them into a language structure with specific features attached. The backdrop knowledge used embraces both the language structure insights and those of the social context, social “landscape”, anthropogenic figurativeness, etc to reach the targeted addressee. The research topicality as considered by the coauthors, involves identifying the usual discourse expansion features which characterize general or specific language “landscape”. The verbs and collocations with a certain role to play in a verbal and cognitive process of discourse expanding, its dynamic changes and mainstream text organization are analyzed as a part of the respective semantic field.